The Impact of Surrogate Advertising on Public Perception and Awareness on Chhattisgarh with Special Reference to Raipur. - Kasturi Pomal; Rakshak Bharti (Feedback International Journal of Communication, 2024)
The industries often argue in defence of advertising their products such as alcohol and tobacco, citing the significant taxes they contribute. Despite the decline in tobacco advertising, both alcohol and tobacco industries continue to promote their products indirectly through surrogate advertisements. These ads often endorse other products under the same brand or present altered versions of the original products, exerting similar influences on consumers' perceptions. The primary objective of this study is to investigate the impact of surrogate advertising, utilizing primary data gathered through surveys to assess public awareness and perceptions. Given India's diverse cultural landscape and demographics, understanding the actual effects of these ads is crucial. It is essential to determine whether the general public comprehends how surrogate advertisements function and whether they can distinguish them from regular advertisements. Ultimately, the focus should be on evaluating the influence of these ads on both the market and individuals and understanding viewers' perspectives on them.